ANALISIS KELAYAKAN FINANSIAL INDUSTRI SIRUP KALAMANSI DI KOTA BENGKULU (STUDI KASUS PADA UNIT USAHA SEGAR ASRI DI KELURAHAN PADANG SERAI, KECAMATAN KAMPUNG MELAYU, KOTA BENGKULU) - Ayunisa, Adelia Putri; Zakaria, Wan Abbas; Kasymir, Eka (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2021)
The purpose of this research was to analyze financial feasibility and sensitivity of calamansi syrup industry in Segar Asri, Padang Serai Village, Kampung Melayu Sub-district, Bengkulu City. This research is a case study conducted in April - May 2019. The location of the research is chosen purposively. Data were obtained from the interview process using a questionnaire. The analytical method used in this research is investment criteria (Internal Rate of Return, Net Present Value, Gross Benefit Cost Ratio, Net Benefit Cost Ratio and Payback Period). The results showed that the financial analysis carried out at Segar Asri, Padang Serai Village, Kampung Melayu Sub-district, Bengkulu City was profitable and feasible to continue. Sensitivity analysis of calamansi syrup industry in Segar Asri, Padang Serai Village, Kampung Melayu Sub-District, Bengkulu City is feasible to continue if there is a decrease in calamansi syrup production by 10%, 20%, and 30%. Key words: Calamansi, feasibility, financial, sensitivity, syrup